Caracterización del Sistema de Tenencia y Morfológica del Ovino Criollo Ecuatoriano en la Provincia de Cotopaxi - Changoluisa Topon, Dilmar Patricio (2018)
This research was carried out in the Cotopaxi province, Latacunga, Saquisilí and Pujilí cities, characterizing the tenure system and the morphology structure of the Creole ovine at the Cotopaxi province as a contribution to its conservation, maintenance and improvement genetic. A survey was applied to 100 breed owners, considering the general data of livestock, human resources, management, and reproduction, among others. 100 animals (92 females and 8 males), older than 3 years old, were sampled. Among the variables measured were (phaneroptic: cephalic profile, orientation of the ears, size of the ears, color of the layer, color of the mucous membranes, color of the hooves, udder pigmentation and udder size, head, encounters, thoracic diameter, length of the rump, bicostal diameter, height at the withers, length of the body). The zoometric cane, inextensible tape measure and the compass of drill bits were used. A descriptive statistical analysis of the data and a simple classification ANOVA and the Tukey test were carried out through the INFOSTAT program. There was little information about the breed, with few records, poor reproductive control and low medical attention, making it difficult to manage the ovine populations. It was determined that the cephalic profile of the Creole sheep is straight in 65%, the orientation of the semierect (100%) and predominantly small (54%) ears. Concerning the color of the layer they were white (87%), with pink mucous membranes (91%) and dark colored hooves (46%). Udders mostly pigmented and of little development. The zoometric variables showed, among other values, elevation at the withers (50.69 cm), length of the head (18.12 cm); bicostal diameter (14.4 cm), longitudinal diameter (56.77 cm) and thoracic perimeter (65.12 cm). Which corresponds to animals of reduced body size compared to other sheep breeds.